Forest transitions: towards a global understanding of land use change - Rudel, Thomas K.; Coomes, O.T.; Moran, E.; Achard, F.; Angelsen, A.; Jianchu Xu; Lambin, E.F. (2005)
Places experience forest transitions when declines in forest cover cease and recoveries in forest cover begin. Forest transitions have occurred in two, sometimes overlapping circumstances. In some places economic development has created enough non-farm jobs to pull farmers off of the land, thereby inducing the spontaneous regeneration of forests in old fields. In other places a scarcity of forest products has prompted governments and landowners to plant trees in some fields. The transitions do little to conserve biodiversity, but they do sequester carbon and conserve soil, so governments should place a high priority on promoting them.